The Influence of Work Motivation and Organizational Communication on Performance of Health Social Security Provider (BPJS) Employees - Taat Kuspriyono; Rianti Setyawasih; Yunidyawati Azlina; Fatkhuri; Syamsulbahri (Sekretariat Pusat Lembaga Komunitas Informasi Teknologi Aceh, 2023)
The aim of this study is to determine the relationship between organizational communication and employee motivation as well as the relationship between organizational communication and employee performance. The study's conclusions indicate that corporate communication has a limited influence on the employee performance variable. The t-test findings, which had a significance level of 0.000 < 0.05 and a t-count value that was higher than the t-table, serve as evidence for this. The results of the t-test with a significance value of 0.000 < 0.05 and a t-count value that is larger than the t-table suggest that work motivation partially proves that it has an effect on employee performance. Both corporate communication and work motivation have a substantial impact on employee performance. This is shown by the results of the f-test, which show an f-count value greater than f-table and a significance value of 0.000 < 0.05.